BLACK WATER NAGARI JOPANG: SEMANGAT MUDA DI TENGAH GELOMBANG OLAHRAGA VOLI NAGARI - alya zuhra ryanto; Halomoan; Salwa Khalisa; Salwa Rizky Meisa; Laily Nafisah; Rechi Inka Candra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The Black Water volleyball team, from Nagari Jopang, Lima Puluh Kota Regency, is a true representation of the spirit of village sports that grows within the local community. This article examines the team's strategic role in sports development, character development for the younger generation, and strengthening social cohesion in the local community. Using descriptive qualitative methods and a participatory approach, it was found that the team's success lies not only in its competitive achievements but also in its ability to build solidarity and active community participation. Black Water's existence serves as an example of how traditional sports at the nagari level can be managed independently and professionally, contributing to character development and a culture of sportsmanship in the region.